Investigating Indian Elementary and Middle School Students’ Images of Designers - Ara, Farhat; Chunawala, Sugra; Natarajan, Chitra (Design and Technology Education: An International Journal, 2013)
This paper presents an investigation into Indian elementary and middle school students’ images of designers. A ‘Draw a designer at work’ test was used with 511 students from Classes 5 to 9 from a school located in Mumbai. Findings from the study indicate that Indian elementary and middle school students, who had no experience in design and technology education (D&T), perceived designers mostly as fashion/ dress designers or artists and designing was associated less with engineering and technology. These results are consistent with an earlier study on Indian middle school students’ ideas about design and designers using written responses, where students demonstrated an incomplete understanding of design and what designers do and associated design with art (Authors, 2011). In the present study students, mostly older ones depicted gender and professional stereotypes. Design as engineering, making or building were mostly associated with male designers and depicted more often by boys. Insights from the study have implications for curriculum development at the school level in India.